MULTILITERATION PEDAGOGIC MODEL BASED ON HIGHER ORDER THINKING SKILL (HOTS) AS EFFORTS TO FACE THE 21st CENTURY EDUCATION IN EDUCATION FROM KI HADJAR DEWANTARA - Sigit Vebrianto Susilo; Ari Yanto (Universitas Sebelas Maret, 2018)
The character of Indonesian education today in practice is a rape of the inner and inner life of children. As a result, children are damaged in character because they always live under duress / pressure. According to Ki Hadjar, such a way of educating will not be able to shape a person until he has a